Legal Analysis of the Dismissal of Village Apparatus in Gorontalo Regency - Ahmad, Fitriyanto Y.; B, Sumiyati; Rusmulyadi, Rusmulyadi (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
The dismissal of village officials is a legal issue that often causes polemics in various regions, including in Gorontalo Regency. This study aims to analyze the legal basis, procedures, and legal consequences of the dismissal of village officials from the perspective of applicable laws and regulations. The research method used is normative juridical research with a statutory approach and a conceptual approach. Data was obtained through a study of laws and regulations such as Law Number 6 of 2014 concerning Villages, Government Regulation Number 43 of 2014, and Regulation of the Minister of Home Affairs Number 83 of 2015 concerning the Appointment and Dismissal of Village Apparatus and its amendments.  The results of the study show that the dismissal of village officials in some cases is not in accordance with legal procedures and good governance principles, thus causing legal uncertainty and violations of the administrative rights of village officials. Stronger supervision and legal understanding from the local government and village heads are needed so that the dismissal process is in accordance with applicable regulations